FREQUENCY OF PERIPHERAL ARTERIAL DISEASE IN PATIENTS PRESENTING WITH ACUTE CORONARY SYNDROME (Journal of Medical & Health Sciences Review, 2025)
Background: Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide, accounting for 7.4 million of 17.9 million annual cardiovascular deaths. Acute coronary syndrome (ACS) is a symptomatic subset of CAD often associated with myocardial infarction, and includes ST-elevation (STEMI) and non-ST-elevation myocardial infarction (NSTEMI). Atherosclerosis is a systemic process; hence peripheral arterial disease (PAD) frequently coexists with CAD as a manifestation of diffuse atherosclerosis. Many CAD patients have coexistent PAD that is asymptomatic and underdiagnosed . Early identification of PAD in ACS patients is important for secondary prevention and risk stratification, but the local frequency of PAD in ACS is not well established.Objective: To determine the frequency of PAD in patients with CAD presenting with ACS to a tertiary care hospital, using ankle-brachial index (ABI) screening, and to analyze associations with patient demographics.Methodology: A cross-sectional study was conducted at the Cardiology Department of a Lady Reading Hospital Peshawar Pakistan. Over a 6-month period from May–Nov 2024, 159 patients aged 40–70 years with ACS (STEMI or NSTEMI confirmed by clinical, ECG and biomarker criteria) were enrolled by consecutive sampling. Patients with previously known PAD, limb deformity, edema, or incompressible arteries (ABI >1.3) were excluded. Demographic data (age, gender, body mass index [BMI], and CAD duration) were recorded. PAD was assessed by measuring ABI using an automated device after 15 minutes of supine rest; PAD was defined as ABI